Implementation of differentiated learning in the Kurikulum Merdeka in class IV - Fajri Anuar; Febrina Dafit (Himpunan Pengembang Kurikulum Indonesia, 2025)
Differentiated learning is learning that accepts and acknowledges readiness and interest in learning so that student learning diversity occurs. The aim of carrying out a differentiated approach is to ensure that students receive an approach that suits their characteristics and needs to maximize their potential and motivate them to learn. This research uses a qualitative approach in its methodology. The instruments used were interviews, observation, and documentation. Triangulation is a data validation technique that compares or checks the correctness of data using sources other than the original data. The validity of the data in this research uses three triangulations: technique, source, and time triangulation. Data and data sources were obtained through observation, documentation, and interviews. Primary data in this research are teachers and school principals. Meanwhile, secondary data used in this research was collected from various sources, including books, journals, papers, and other supporting materials. The results of the study concluded that there are several stages in differentiated learning, namely mapping students' needs through diagnostic assessments, designing differentiated learning plans according to students' needs by implementing content, process, and product strategies, and evaluating and reflecting on the learning that has been implemented. Abstrak Pembelajaran berdiferensiasi ialah pembelajaran yang menerima serta mengakui dengan adanya kesiapan dan minat belajar sehingga terjadilah keberagaman belajar peserta didik. Tujuan dilakukannya pendekatan berdiferensiasi supaya peserta didik menerima pendekatan yang sesuai dengan karakteristik serta kebutuhan peserta didik untuk memaksimalkan potensi serta memiliki motivasi dalam pembelajaran. Penelitian ini menggunakan pendekatan kualitatif dalam metodologinya. Instrumen yang digunakan berupa wawancara, observasi dan dokumentasi. Triangulasi adalah teknik validasi data yang membandingkan atau memeriksa kebenaran data dengan menggunakan sumber selain data asli. Dan keabsahan data dalam penelitian ini menggunakan 3 teknik triangulasi yakni triangulasi teknik, sumber dan waktu. Data dan sumber data didapatkan melalui observasi, dokumentasi dan wawancara. Data primer pada penelitian ini adalah guru dan kepala sekolah. Sementara data sekunder yang digunakan dalam penelitian ini dikumpulkan dari berbagai sumber, antara lain buku, jurnal, makalah, dan bahan pendukung lainnya. Hasil penelitian disimpulkan bahwa terdapat beberapa tahapan dalam pembelajaran berdiferensiasi yaitu melakukan pemetaan kebutuhan peserta didik melalui asesmen diagnostik, merancang perencanaan pembelajaran berdiferensiasi sesuai kebutuhan peserta didik dengan mengimplementasikan strategi konten, proses, dan produk, melakukan evaluasi dan merefleksi pembelajaran yang sudah dilaksanakan. Kata Kunci: kurikulum merdeka; pembelajaran berdiferensiasi; penerapan kurikulum